PENGARUH BAHASA IBU TERHADAP KETERAMPILAN KOMUNIKASI BAHASAINDONESIA ANAK DALAM PEMBELAJARAN - Fatimatuzzahra; Idawati; Febriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mother tongue is the first language acquired by children from the surrounding environment. Because it is the language that children initially acquire and use to communicate with their environment, and the growth of knowledge, experience and communication are all greatly influenced by language as a component of their daily lives. Being the language that applies in the country, Indonesian is used in all official processes, including the learning process. This makes learning Indonesian much more difficult and allows for language mixing due to the influence of the mother tongue. Therefore, in this article we will discuss the influence of the mother tongue. This research uses a descriptive qualitative approach. Not only students participate in language mixing events, but also teachers. The mother tongue has been ingrained in students since childhood. This incident occurred when Indonesian was used as a substitute for the mother tongue, which naturally and spontaneously combined the two languages. And as a result, the structure of the Indonesian language becomes damaged. Keywords: child, mother tongue, comunication